Abject desires in Lisa See’s Peony in Love - Poh, Chin Koon; Mohammad Ewan Awang,; Arbaayah Ali Termizi,; Ching, Florence Toh Haw (Penerbit Universiti Kebangsaan Malaysia, 2021)
The establishment of the Manchu led-Qing dynasty in 1636 led to the continuation of Confucianism as the dominant belief system in China. Based on these Confucian principles of patrilineality and patrilocality, women were expected to portray exemplary feminine virtues that required them to remain subservient and obedient to the men in her family. This oppressive practice placed women lower in the hierarchy as, unlike men, they were denied the means and avenue to express their subjectivities and, consequently, had to repress their desires to conform to a collective identity. Female desires are viewed as a form of abject as they do not conform to the female codes of behaviour assigned by the patriarchal system. To follow their desires would mean going against the gender norms of the society. As such, women’s desires are attributed abject qualities due to their ability to disrupt the boundaries of the dominant system and are thus subject to censorship. Lisa See’s Peony in Love (2007) depicts the struggles and predicament of Chinese women who had to repress their desires due to their gender. Using Julie Kristeva’s concept of the abject, this study intends to examine how the female protagonist, Peony negotiates her position within the patriarchal setting to reclaim her sense of identity. According to Kristeva, the abject can distort boundaries due to its transgressive nature. For this reason, the study will set out to identify representations of abject desires and their implications on Peony. This study argues that it is through these representations of abject desires that enable Peony to subvert the patriarchal boundaries and reclaim her sense of identity.